2016
DOI: 10.1080/15298868.2016.1241822
|View full text |Cite
|
Sign up to set email alerts
|

Implications for the self determine benevolence and self-protection in intergroup relations

Abstract: People often favor groups they belong to over those beyond the in-group boundary. Yet, in-group favoritism does not always occur, and people will sometimes favor an out-group over the in-group. We delineate theoretically when in-group favoritism (i.e., self-protection) and out-group favoritism (i.e., benevolence) should occur. In two experiments, groups’ relative status and competence stereotypes were manipulated; groups’ outcomes were non-contingent in Experiment 1 and contingent in Experiment 2. When allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Benevolence Uniqueness Value (BUV) as considered as the local wisdom of destination is closely related with Revisited Cultural Heritage (RCH) with CR (5,727). The tourists are attracted and obtained unforgettable experiences from local people hospitalities as H2 is accepted (Malloy & Kinney, 2017;Shaw et al, 2020;Svare et al, 2019).…”
Section: Hypotheses Testing and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benevolence Uniqueness Value (BUV) as considered as the local wisdom of destination is closely related with Revisited Cultural Heritage (RCH) with CR (5,727). The tourists are attracted and obtained unforgettable experiences from local people hospitalities as H2 is accepted (Malloy & Kinney, 2017;Shaw et al, 2020;Svare et al, 2019).…”
Section: Hypotheses Testing and Findingsmentioning
confidence: 99%
“…The significant relationship between Benevolence Uniqueness Value and Architectural Heritage Preferences is also accepted with CR (5,227). The local people hospitality, benevolence and uniqueness are becoming the attractive determinants factors to revisit and put the architectural heritage to the list to visit (Lin et al, 2021;Malloy & Kinney, 2017). For more details, see the following Table 3.…”
Section: Hypotheses Testing and Findingsmentioning
confidence: 99%
“…There are two possible sources of the bias. Malloy and Kinney (2014) showed that during reward allocation, high status members (arbitrarily made though a minimal group paradigm) will often select the out-group members to receive a beneficial outcome if they do not see them as threatening to their own economic resources. Within the context of the current study, particularly for Low Afrocentric/White arrays, Low Afrocentric candidates (low status)…”
Section: Out-group Positivity Biasmentioning
confidence: 99%
“…The percentage of women victims and crimes has become increasingly larger as more and more sale of self-protection devices records rapid growth. Therefore, the development of self-protection device for women which not only can be detected dangerous person in advance in case of going a woman alone in the middle of nowhere late at night but can prevents crimes is necessary [3], [4]. Firstly, user should establish a range of approaching to operate alarm sensor within the range and vibration or alarm sound is to inform user while sensing time and its location are transmitted guardian when the sensor is operating.…”
Section: Introductionmentioning
confidence: 99%